2020
DOI: 10.1136/annrheumdis-2020-219113
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Italian patients with rheumatic autoimmune systemic diseases

Abstract: Patient and public involvement Patients and/or the public were not involved in the design, or conduct, or reporting or dissemination plans of this research. Patient consent for publication Not required. Provenance and peer review Not commissioned; internally peer reviewed. This article is made freely available for use in accordance with BMJ's website terms and conditions for the duration of the covid-19 pandemic or until otherwise determined by BMJ. You may use, download and print the article for any lawful, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Surveillance bias due to increased awareness and testing of our patients because of their rheumatic diseases and immunosuppression could have led to increased identification of COVID‐19 in our cohort. An Italian study indicated a similar increase in the prevalence of COVID‐19 in patients with systemic autoimmune diseases (9). Smoking may be a confounder and was not assessed in this study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Surveillance bias due to increased awareness and testing of our patients because of their rheumatic diseases and immunosuppression could have led to increased identification of COVID‐19 in our cohort. An Italian study indicated a similar increase in the prevalence of COVID‐19 in patients with systemic autoimmune diseases (9). Smoking may be a confounder and was not assessed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Initial reports (8) revealed no unique or outstanding risk factors, apart from what has already been noted in the general population. An Italian study indicated a possible increased incidence of COVID‐19 in patients with rheumatic diseases (9).…”
Section: Introductionmentioning
confidence: 99%
“…They both showed an incidence of 2.5%, although in patients affected by systemic lupus erythematosus and large-vessel vasculitis, respectively [ 9 , 10 ]. It has been hypothesized by others that patients suffering from connective tissue diseases could run a higher risk of COVID-19 than those with inflammatory arthritis [ 11 ]. Thus, considering the demographic data of the different cohorts, the relevant element seems to be the belonging geographical area of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Akiyama et al also evaluated the results from six case-control studies that demonstrated that the risk of COVID-19 in patients with RA was significantly higher than in the control groups (OR: 1.6; 95% CI: 1.1-2.3; p = 0.008) [104]. When interpreting results, it is important to consider that observational data may underestimate infection risk, as patients will often be aware of the risks inherent to their disease and may have adapted their lifestyle to reduce the probability of contracting COVID-19 [105].…”
Section: Infections Inmentioning
confidence: 99%